EFFICIENT HYDROALCOHOLIC EXTRACTION FOR HIGHEST DIOSGENIN CONTENT FROM TRILLIUM GOVANIANUM (NAG CHHATRI) AND IT’S IN VITRO ANTICANCEROUS ACTIVITY - Sood, Hemant; Sharma, Shivam; Sharma, Arun; Mehta, Vineet; Chauhan, Rajinder Singh; Malairaman, Udayabanu (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The present study involves hydroalcoholic extraction of Trillium govanianum (Hindi name: Nag chhatri), which is a high-value medicinal plant found at the altitude of 2500-4000 m. Aiming in this direction, we performed hydrolysis of extract using response surface methodology (RSM) for optimizing diosgenin content. The extracts were evaluated for cytotoxicity. Methods: In RSM, the cumulative effect of independent variables including time (minutes), temperature (Â°C), and solid-liquid ratio (g/ml) were investigated through central composite design. Cytotoxicity studies of crude rhizome and hydroalcoholic extract were carried out by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay on three cell lines, viz., MDCK, MCF-7, and MDA-MB-23. Results: The diosgenin content obtained was 5.9%, which is reported for the first time in T. govanianum. Hydrolyzed extract showed less toxicity in MDCK (normal cell line) cells but significantly reduced the proliferation of MCF-7 and MDA-MB-231 cancer cells. Conclusion: Hydrolysis method was optimized by RSM, which proved to be an efficient method for extraction of diosgenin from T. govanianum. Hydrolyzed extract showed antiproliferative activity on cancer cell lines with minimal effect on normal cells. Keywords: Trillium govanianum, Diosgenin, Nag chhatri, Hydrolysis, MDCK, MCF-7, MDA-MB-231.